Quick Synthesis of SnS Nanoparticles. (2018) - Dutta, P.K.; Mitra, S.
Abstract: SnS nano-particles are synthesized wet chemically using SnCl2 .2H2 O (tin(II) chloride) as Sn source and C2 H5 NS (thioacetamide) as S source in aqueous triethanolamine. Ammonia solution is used to maintain the pH ∼12 at room temperature. This step produces dark brown SnSx (x>1), which is bath sonicated with occasional stirring for 20 minutes for preventing the particles from agglomerating, followed by washing, drying and annealing at 500 °C in N2 atmosphere for 1 hr to obtain nearly phase pure SnS. The as-prepared SnS exhibits spherical morphology with average particle size in the range of 30 to 60 nm